Watching is One of the Forgotten Linguistic Novel Methods - Kamel, Ass Prof Dr.Qassim Mohmmed (Thi Qar Arts Journal, 2024)
Linguists needed to combine the language in order to serve the Holy Qur’an and the noble hadith, with a sincere desire to preserve the language of the Arabs, so they adopted the methods of those who preceded them, especially those who read and hadith, so that the narrator is trustworthy, the chain of transmission is connected, and the text is straight, and that the narrator takes the narration directly by hearing from the Arabs. Or the narration from those who were quoted by one of the following methods:1- Hearing the Sheikh’s recitation.2- Hearing the narrator’s recitation to the sheikh.3- Hearing someone else recite it to the sheikh while he was listening.4- Munawala, which is when the sheikh hands him a book that he has written or narrated to others, and allows him to narrate it.5- Al-Wajada, which is taking the lines of trustworthy people with confidence in their knowledge, and what they are known for in terms of accuracy and mastery.As for what happened after that, they do not take it into account, such as taking from newspapers, because it missed the condition of accuracy in transmission, due to ignorance of the knowledge of those who narrated it or reproduced it.      However, the scholars neglected another method that they did not mention among the methods of transmitting the language despite the presence of its wide effects in their narratives. Linguists use it in detailing what they witnessed of animals, plants, and inanimate objects, what was mentioned and was not detailed in it, and what was not mentioned, so it needs detailing. the present, and how it possessed sufficient tools to convey the meanings of words to the listener, and to draw the shades around them that enabled them to reach his mind, until the matter ended with what the illustrated dictionaries have concluded today, and if it were not for them, many words would have become ambiguous and devoid of the significance that pours into it the soul, and broadcasts in it life, and bring it closer to the reader.